VD_FINDINFO HC / 2013 / 17 vom 7. Januar 2013 - VD Tribunal cantonal (2013)
BAIL À LOYER, RÉSILIATION, PROLONGATION DU BAIL À LOYER, PROTECTION CONTRE LES CONGÉS | 2 al. 1 CC, 2 al. 2 CC, 4 CC, 271 al. 1 CO, 272 CO, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 317 al. 1 CPC (CH)